University Undergraduates` Value Priorities and Lifestyle in Osun State - Yusuf, Hamdallat Taiwo (International Journal Pedagogy of Social Studies, 2020)
This study examined the relationship between value priorities and lifestyle of university undergraduates in Osun State. A descriptive survey was adopted, and 300 undergraduates served as the sample for this study. The study has three research questions, with questions one and two answered with the mean rating. In contrast, research question three had the corresponding hypothesis analysed with the Pearson Product Moment Correlation (PPMC) at 0.05 level of significance. Findings revealed that self-direction, security, achievement, stimulation, power, tradition and conformity were the values prioritised among university undergraduates. This study recommended, among others, that parents should make efforts to educate their children on the right type of values and motivate them to know their importance to shape their lifestyles positively.